Analog Signal and Digital Signal Processing in Telecommunication System - Phong Hung; Vu Duc Vuong (Newinera Publisher, 2020)
The term digital signal is a term from a technology that converts an analog signal into digital data so that the signal can be processed more easily and quickly. The term digital itself is a system that only recognizes two conditions. The two conditions are usually represented by the numbers zero and one, on and off, or others. The smallest unit of digital signal is the bit.